(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2023)
Bagworm, Thyridopteryx ephemeraeformis Haw. (Lepidoptera: Psychidae) is a polyphagous pest in Northern America and southern Australia, causing severe damage to several host plants. A study was conducted to record the host plants, damage extent, and morphometrics of bagworms in Patuakhali Science and Technology University (PSTU) from 2015 to 2018. Results revealed a limited number of host plants for bagworm namely guava (Psidium guajava), arborvitae/juniper (Thuja standishii), rangan or jungles, geranium (Ixora grandiflora/Ixora coccinea), mussaenda (Mussaenda philippica), cropperleaf (Acalypha wilkesiana ‘Ceylon), henna (Lawsonia inermis), mango (Mangifera indica), pomegranate (Punica granatum) and betel nut (Areca catechu). The length of tiny larvae, fully-grown larvae, pupa, adult winged male moths, and wingless adult maggot-like females was 1.02 mm, 24.8 mm, 14 mm, 15 mm, and 48 mm, respectively. The average length of the bag was 24.7 mm with a range of 21-28 mm, and the average breadth in the middle of the bag was 6.9 mm with a range of 6-8 mm. The highest number of larval cases per branch was found in guava (56), and the lowest was in copperleaf (8). The highest percent of leaf damage (86.23%) per plant was also observed in the guava plant, and the lowest percent of leaf damage (37.46%) was in copperleaf. The highest number of infested leaves and bags per leaf was observed in the lower stratum of the guava branch, while the lowest infestation was in the top stratum. The highest percentage of leaf area (30%) damage was recorded 72 hours after release (HAR), and the lowest percentage of leaf area (10%) damage was at 24 HAR in guava. The maximum amount of leaf was consumed by bagworm larva at 72 HAR and the minimum amount was consumed at 24 HAR in guava. The maximum leaf area (13.46 cm2) consumption was recorded at 72 HAR, while the minimum amount (3.42 cm2) was consumed at 24 HAR. No significant damage by T. ephemeraeformis was observed in the case of mango, pomegranate, and betel nut plants. J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 1-17, June-December 2022